2013
DOI: 10.1097/coh.0000000000000009
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline of drugs for related diseases

Abstract: Purpose of review For the first time in decades, there are multiple new drugs in the pipeline for the treatment of tuberculosis (TB). In addition, existing drugs are being repurposed or optimized for TB with the goal of shortened treatment duration for drug-sensitive TB and safer, shorter treatments for multidrug-resistant (MDR) TB. In this review, the results of recent trials evaluating novel combination regimens for TB disease and latent TB infection are described. Recent findings High-dose rifamycins (rif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Preclinical as well as clinical studies have demonstrated that rifamycins have dose-dependent activity and that current dosing achieves concentrations that are on the steep part of the dose-response curve (22,23). Rifamycins have significant potential for shortening TB treatment (21,24,25), and recent trials have demonstrated that within the range of doses tested clinically, higher doses of rifamycins improve microbiologic outcomes significantly (26,27). Other clinical studies also suggest that increasing rifampin concentrations can hasten sterilization (28) in TB treatments and that low rifampin concentrations lead to acquired drug resistance (29).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical as well as clinical studies have demonstrated that rifamycins have dose-dependent activity and that current dosing achieves concentrations that are on the steep part of the dose-response curve (22,23). Rifamycins have significant potential for shortening TB treatment (21,24,25), and recent trials have demonstrated that within the range of doses tested clinically, higher doses of rifamycins improve microbiologic outcomes significantly (26,27). Other clinical studies also suggest that increasing rifampin concentrations can hasten sterilization (28) in TB treatments and that low rifampin concentrations lead to acquired drug resistance (29).…”
Section: Discussionmentioning
confidence: 99%
“…With limited pharmacological discoveries in the past 4 decades, the advent of new strategies for active TB disease is encouraging for TB prevention and control. 72 Current research trials are investigating the use of the 12-dose INH and RPT regimen by DOT in low-income countries with high TB prevalence, as well as the actual cost-effectiveness and safety of using new regimens in clinical practice. 70 Along with the scientific advancements in diagnostic measures and multipharmaceutical regimens based on the infectious etiology of LTBI, the influence of social determinants of health on LTBI transmission and prevention may be key to global control of LTBIs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MDR-TB have an increased likelihood of treatment failure or death and are more likely to develop additional drug resistance [10]. Therefore, there is a compelling need for new anti-TB drugs that are more effective and better tolerated, and can shorten the duration of therapy [3,4,7,10]. Shorter treatment duration reduces the cost of therapy, improves adherence and helps prevent drug resistance [7].…”
Section: Place Of Delamanid In the Treatment Of Multidrugresistant Tumentioning
confidence: 99%
“…Therefore, there is a compelling need for new anti-TB drugs that are more effective and better tolerated, and can shorten the duration of therapy [3,4,7,10]. Shorter treatment duration reduces the cost of therapy, improves adherence and helps prevent drug resistance [7]. New MDR-TB regimens should include drugs to which resistance is not expected to have developed, thereby avoiding dependence on drug susceptibility testing [4].…”
Section: Place Of Delamanid In the Treatment Of Multidrugresistant Tumentioning
confidence: 99%
See 1 more Smart Citation